Nuclear VPS35 attenuates NHEJ repair by sequestering Ku protein - Luping Zhang; Yonghong Nie; Tuo Tang; Yanji Lu; Wenlong Li; Xian Hong; Qiang Li; Aixue Zheng; Yongpei Li; Jianwen Zhou; Li Fan; Tao Wang; et al. (Molecular Medicine)
Abstract Vacuolar protein sorting-associated protein 35 (VPS35), a pivotal constituent of the retromer complex, mediates the retrograde trafficking of endosomal cargoes in the cytoplasm. Intriguingly, VPS35 displays a dual localization pattern, residing both in the cytoplasm and the nucleus, but its nuclear role remains elusive. In this study, we unravel a nuclear function of VPS35, demonstrating it impedes DNA repair by inhibiting non-homologous end joining (NHEJ). Mechanistically, VPS35 interacts with the Ku protein, sequestering it away from DNA damage sites. Consequently, nuclear VPS35 halts the activation of DNA-PKcs, hindering the recruitment of XLF and DNA-Ligase 4, ultimately suppressing NHEJ efficiency. Furthermore, in response to DNA damage, VPS35 dissociates from Ku protein and orchestrates a strategic relocation from the nucleus to the cytoplasm. Thus, our findings suggest VPS35 attenuates NHEJ repair by restricting Ku protein availability at DNA damage sites, offering a potential avenue for fine-tuning DNA repair efficiency.